PENERAPAN GREEN CHEMISTRY PADA DETEKSI KANDUNGAN PEWARNA BERBAHAYA (RHODAMIN B) PADA PRODUK KOSMETIK YANG BEREDAR DI WILAYAH PEKALONGAN - Kharimatul Khasanah; Siska Rusmalina; Dhea Safira; Eka Ari Setyorini; Nila Amanah (LPPM Universitas Pekalongan, 2022)
Cosmetics play an important role for a woman so that many women do various ways to beautify themselves, including by using cosmetics. In the era of globalization, people's cosmetic needs are increasing, so the circulation of cosmetic products tends to increase. This triggers competition among producers to offer superior products that can attract consumers. This competition is the cause of the emergence of unscrupulous producers to abuse active substances that are prohibited in cosmetics such as rhodamine B dye. its use is prohibited because the impact can be detrimental to the user. The purpose of this study was to determine the Rhodamine B dye in cosmetic preparations in several types of preparations circulating in the Pekalongan Region. In this study, descriptive research method was used, namely qualitative identification of samples in the laboratory using thin layer chromatography to determine the presence of Rhodamine B dye by applying the concept of Green Chemistry. In principle, Green Chemistry is an effort to apply research methods that develop chemical processes and environmentally friendly chemical products. The results of the study stated that from 17 samples, 3 samples were declared positive for containing Rhodamine B in the samples coded BB, LC and ED. The research results obtained can be used as a reference for the public to be more careful and thorough in choosing cosmetics.